The ultimate guide to cheerleading for cheerleaders and coaches - Wilson, Leslie
The Ultimate Guide to Cheerleading has everything you need to be successful participant in cheerleading, be it as a team member of coach. Written for both novices and those experienced in the cheerleading game, inside is all the essential information you need for fun and success, including: step-by-step photos of game cheering, jumps, stunting, pyramids, and more; specific activities to prepare for tryouts and improve skills throughout the season; routine choreography and other creative ideas; important coaching guidelines and safety information; tips on how to start a cheerleading program from scratch and much, much more!